2008
DOI: 10.1074/jbc.m708825200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a New Family of Genes Involved in β-1,2-Mannosylation of Glycans in Pichia pastoris and Candida albicans

Abstract: Structural studies of cell wall components of the pathogenic yeast Candida albicans have demonstrated the presence of ␤-1,2-linked oligomannosides in phosphopeptidomannan and phospholipomannan. During C. albicans infection, ␤-1,2-oligomannosides play an important role in host/pathogen interactions by acting as adhesins and by interfering with the host immune response. Despite the importance of ␤-1,2-oligomannosides, the genes responsible for their synthesis have not been identified. The main reason is that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 60 publications
0
68
0
3
Order By: Relevance
“…Indeed, we did not find an ortholog of the S. cerevisiae gene MNN1 (encoding the alpha-1,3-mannosyltransferase) in the Pichia genome. However, Pichia glycoproteins can in some cases be modified with b-1,2-mannose residues 30 , reminiscent of antigenic epitopes on the Candida albicans cell wall 31 . We find the patented P. pastoris AMR2 b-mannosyltransferase in the genome, and three homologs, thus providing the basis for reducing the levels of this undesired glycan modification.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we did not find an ortholog of the S. cerevisiae gene MNN1 (encoding the alpha-1,3-mannosyltransferase) in the Pichia genome. However, Pichia glycoproteins can in some cases be modified with b-1,2-mannose residues 30 , reminiscent of antigenic epitopes on the Candida albicans cell wall 31 . We find the patented P. pastoris AMR2 b-mannosyltransferase in the genome, and three homologs, thus providing the basis for reducing the levels of this undesired glycan modification.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the oligosaccharide is one of the virulence factors in Leishmania species as well as Candida species, and that enzymes involved in the synthesis are potential targets for new therapies for these infections. Recently, Mille et al 25) identified the b-1,2-mannosyltransferase gene family in C. albicans. They showed that none of these sequences contains the conserved sugar-binding region containing the DXD (D, aspartic acid; X, any amino acid) motif (pfam Gly_transf_sug; PF04488) found in many families of glycosyltransferases.…”
Section: Resultsmentioning
confidence: 99%
“…majorité des mannoprotéines de paroi. Les raisons pour lesquelles ce système est aussi complexe restent inconnues, mais son existence suggère une certaine importance biologique pour C. albicans [17], d'autant que, selon des mécanismes qui restent obscurs, les anticorps anti-β-mannosides protègent des candidoses expérimentales vaginales et systémiques.…”
Section: La Maladie De Crohnunclassified